(untitled) (Revista Iberoamericana de Bioética, 2021)
This paper addresses the different discussions that led to the creation of the NeuroRights Initiative and the proposal for a NeuroRight to equal access to mental augmentation. Then it presents some conceptual clarifications, and subsequently makes a detailed analysis of the proposal in light of posthumanism. In this sense, it studies how this NeuroRight may lead to inequality, loss of social diversity and pressures on sociocultural and religious diversity. It also studies the problems and challenges inherent to the implementation of this type of initiative. We propose that a NeuroRight to enhancement should not be incorporated and that equitable access to technologies should be limited to therapeutic purposes only.